THE INFLUENCE OF EASTERN PHILOSOPHY ON WESTERN LITERATURE - Qadamova Ruhshona Habibullayevna; Matjonova Qurvonbika O‘rinboyevna; Abdurakhmanova Diana Valerevna (TADQIQOTLAR.UZ, 2024)
Abstract: This thesis explores how Eastern philosophy has influenced Western literature, focusing on the key philosophical ideas from Hinduism, Buddhism, Taoism, and Confucianism that have been integrated into the works of notable Western authors. By  analyzing  the  contributions  of  Transcendentalism,  Modernism,  Postmodernism, and contemporary literature, the paper shows how Eastern thought has helped reshape Western literary narratives. Key figures such as Ralph Waldo Emerson, T.S. Eliot, and Hermann  Hesse  are  examined  to  highlight  this  cross-cultural  exchange.  The  study concludes  by  showing  the  continued  impact  of  Eastern  philosophies  on  the  global literary landscape.